Exploring the Impact of Accommodation and Transportation on Tourist Satisfaction：Literature Review - Yan Jie; Alyaa Afifah Abu Talib (Journal of Current Research and Studies, 2024)
This research aims to explore the impact of accommodation and transportation on tourist satisfaction through literature review. With the rapid development of tourism, accommodation and transportation, as the two basic elements of tourism activities, have an important impact on the overall experience and satisfaction of tourists. This paper first reviews the existing research results on the impact of accommodation quality, location selection, service level and cultural immersion on tourist satisfaction. The comfort, cleanliness, value for money and the ability to offer a unique cultural experience are all key factors influencing visitor satisfaction. At the same time, the convenience, comfort and safety of transportation also significantly affect the travel experience of tourists. This article focuses on emerging trends in the accommodation and transportation sector, such as sustainable accommodation, the application of intelligent technology, and the provision of personalized services. These emerging trends not only improve the quality of accommodation and transportation services, but also bring a richer and more diverse travel experience to tourists. Finally, this paper summarizes the main findings of the impact of accommodation and transportation on tourist satisfaction, and points out that future studies should further explore the optimization strategies of accommodation and transportation services and how to better meet the needs of different tourist groups. At the same time, for tourism managers and practitioners, attention should be paid to the improvement of accommodation and transportation services to improve tourist satisfaction and promote the sustainable development of tourism.